1991
DOI: 10.1073/pnas.88.19.8686
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-induced fluid-phase immiscibility in membranes.

Abstract: The fluid-phase behavior of binary mixtures of cholesterol with phosphatidyichoilnes is investigated using magnetic resonance methods. Phospholipid biradicals provide the electron spin resonance spectroscopic resolution of two Immiscible fluid phases in the dlpalmitoylphosphatidylcholinecholesterol system. Isotropic chemical shifts of the phospholipid carbonyl carbons in binary mixtr with cholesterol measured using solid-state high-resolution nuclear magnetic resonance methods furnish evidence for a putative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
251
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(271 citation statements)
references
References 23 publications
16
251
0
2
Order By: Relevance
“…Available data from many experimental studies of the plasma membrane in general suggest cholesterol is the driving force for microdomain formation and cholesterol is not uniformly or homogeneously distributed but that the plasma membrane of living cells consists of areas of cholesterol segregation (regions that are cholesterol-rich and cholesterol-poor) (56,214). Biochemical studies also support this concept and demonstrate that purified cholesterol-rich microdomains isolated from cultured cell (L-cell, MDCK, primary hepatocytes) represent nearly one-third of the plasma membrane, are rich in cholesterol as well as saturated/ monounsaturated fatty acylated phospholipids, and are comprised of physically distinct, liquidordered membrane phases intermediate between fluid liquid-crystalline and rigid gel phases (26,82,102,136,172,182,(215)(216)(217).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Available data from many experimental studies of the plasma membrane in general suggest cholesterol is the driving force for microdomain formation and cholesterol is not uniformly or homogeneously distributed but that the plasma membrane of living cells consists of areas of cholesterol segregation (regions that are cholesterol-rich and cholesterol-poor) (56,214). Biochemical studies also support this concept and demonstrate that purified cholesterol-rich microdomains isolated from cultured cell (L-cell, MDCK, primary hepatocytes) represent nearly one-third of the plasma membrane, are rich in cholesterol as well as saturated/ monounsaturated fatty acylated phospholipids, and are comprised of physically distinct, liquidordered membrane phases intermediate between fluid liquid-crystalline and rigid gel phases (26,82,102,136,172,182,(215)(216)(217).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Detailed phase diagrams of cholesterol in membranes have been constructed by various groups (Lentz et al, 1980;Sankaram & Thompson, 1991;Huang et al, 1993). In the DPPC/cholesterol system, cholesterol has been proposed to be freely distributed in the bilayer at very low concentrations (<5 mol %).…”
Section: Discussionmentioning
confidence: 99%
“…Such changes might include alterations in the hydrogen-bonding interactions thought to occur in chain-ordered SM (Bruzik, 1988;Sankaram & Thompson, 1991;Bittman et al, 1994). Interestingly, McIntosh et al (1992b) reported that the presence of equimolar cholesterol in SM bilayers alters the hydration pressure relative to that of pure SM bilayers.…”
Section: Cholesterol's Condensation Of Sms and Galcers With Identicalmentioning
confidence: 99%
“…Speyer et al (1989) and Morrow et al (1995)]. In doing so, transient acyl kinks, which enhance the molecular crosssectional area in the hydrocarbon region proximal to the lipid interface, become diminished so that optimal van der Waals interactions can be achieved between the hydrocarbon chain(s) and the α surface of the steroid ring which is held near the interface by a 3-β hydroxyl group (McIntosh et al, 1992a;Vanderkooi, 1994) and may hydrogen bond with the amide group of the sphingolipid (Sankaram & Thompson, 1991;Bittman et al, 1994). Because the cross-sectional area of cholesterol undergoes almost no change in response to increasing surface pressure, the bulk of the condensing effect induced by cholesterol must be due to ordering that occurs in the sphingolipid hydrocarbon region.…”
Section: Cholesterol's Condensation Of Sms and Galcers With Identicalmentioning
confidence: 99%
See 1 more Smart Citation